Sistem Pendukung Keputusan berbasis Web dalam Pengangkatan Pekerja PKWT Menjadi Pekerja Tetap - Chaniago, Audiya Ananda; Siddik, Mohd; Muhazir, Ahmad (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
The uncertainty of the status of certain time work agreement (PKWT) workers, the appointment of which is still done manually, takes a long time, thus causing certainty problems among workers at CV. Pelita Berjaya Bersama. This study aims to design a decision support system for the appointment of non-permanent workers to permanent workers using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. This research chose a structured and linear waterfall development model, ensuring each stage of development is completed sequentially with complete documentation. The system was developed by going through the stages of requirements gathering, architecture design (database, interface, AHP, and SAW algorithms), design realization (PHP code writing and MySQL database development), and testing using a black box to ensure the system functions properly. The result of our findings is a decision support system that can help companies in making decisions objectively and simplify the appointment process. The system produces output data in the form of ranking results from each alternative so that it is easy to understand. The use of AHP and SAW algorithms in the system is expected to increase accuracy in the selection process. The results of system testing using black box are declared successful starting from the login to logout process. With this system, the company can appoint PKWT workers to become permanent workers.